Spirituality-based action competence for sustainability among prospective biology teacher in Indonesia - Abdulkadir Rahardjanto; H. Husamah; Samsun Hadi; Nurdiyah Lestari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
As a form of implementing Education for Sustainable Development (ESD) in educational institutions, an appropriate learning model is needed, which also accommodates aspects of spirituality. Before developing a model, baseline data is needed, so a broad-scale or national needs analysis is needed. This research aims to determine the profile of spirituality-based action competence for sustainability (ACS) among prospective biology teacher students throughout Indonesia. This research is a cross-sectional survey. The target respondents are students of LPTK biology education study programs in Indonesia. The target population size is 650 people, so based on the Krejcie and Morgan table, the minimum sample size with a confidence level of 95% and a margin of error of 5% is 620 students. The data collection instrument used in this research is the action competence for sustainability instrument based on spirituality (ACSIS). Data on respondent characteristics were analyzed using frequencies and percentages. The mean and standard deviation of scores were calculated for each item. Comparisons of two groups of students were analyzed using the Mann-Whitney U Test, while comparisons of more than two groups used the Kruskal-Wallis H Test. We discuss interesting findings in this research, including the aspects of spirituality in ACS among prospective biology teacher in Indonesia.